Challenges of Nordic labour markets: A polarization of working life? - Rita Asplund; Erling Barth; Per Lundborg; Kjersti Misje Nilsen (The Research Institute of the Finnish Economy (ETLA), 2011)
Labour-market polarization is characterized by increased employment in occupations at the top but also at the bottom of the skills and wage distributions, followed by a relative decline in 'middling' occupations. This paper documents a polarization trend also in the Nordic labour markets and contrasts it to comparative findings for the USA. Employment growth in the top-paying occupations is found to have been dominated by a large increase in the category of 'Engineering professionals and other professionals', whereas the growth at the bottom end stems mainly from increased employment in 'Personal and protective services'. The drop in the middle has been driven by a marked relative decline in the category 'Office clerks'. Analysis of the extent to which differences in wage development across skill groups have enhanced or attenuated this process of polarization in employment patterns suggests that the U-shaped pattern of employment change prevails also after controlling for concomitant changes in relative occupational wages. Hence, it seems that also the Nordic countries have experienced a shift from skill-biased technological change to non-routine-biased technological change - or, more likely, a combination of the two - and that this process has not been particularly dampened by compressed wage structures or relatively more rigid wages.
Keywords: J21; J23; J31; 330; Labour market; polarization; occupation; relative wages; Lohnstruktur; Berufsstruktur; Arbeitsmarkt; Finnland; Norwegen; Schweden